Observations on some spawning grounds of the Gangetic major carps with a note on carp seed resources in India - David, A (Indian Journal of Fisheries, 2016)
Eventhough Labeo rohita (Hamilton), Catla catla (Hamilton) and Cirrhina mrigala (Hamilton) are the three most important of the cultivable carps in the freshwater ponds of India, definite information as to their spawning movements and actual spawning grounds in riverine habitats is still lacking. Since these species breed in rivers and streams along with other uneconomic and predatory fishes, such knowledge is considered of primary importance for the collection of pure quaUty of their ’ spawn’â€”(larval stages), fry and fingerlings, which is an essential prerequisite for successful piscicultural operations.